2019
DOI: 10.1002/tox.22817
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants (POPs) increase rage signaling to promote downstream cardiovascular remodeling

Abstract: Exposure to environmental contaminants and consumption of a high, saturated fatty diet has been demonstrated to promote precursors for metabolic syndrome (hyperglycemia, hyperinsulinemia, and hypertriglyceridemia). The purpose of this study was to determine if exposure to the most prevalent environmental persistent organic pollutants (POPs) would act as causative agents to promote metabolic syndrome independent of dietary intake. We hypothesized that POPs will activate the advanced glycated end‐product (AGE)‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…Similarly, elevated levels of transnonachlor have been linked to clinical manifestations of atherosclerosis, compromised glycemic control, and impaired beta cell function . Exposure to OC mixtures in mice has also shown to be able to intensify oxidative and inflammatory stressors in the heart to overwhelm protective mechanisms allowing for adverse cardiac remodeling …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, elevated levels of transnonachlor have been linked to clinical manifestations of atherosclerosis, compromised glycemic control, and impaired beta cell function . Exposure to OC mixtures in mice has also shown to be able to intensify oxidative and inflammatory stressors in the heart to overwhelm protective mechanisms allowing for adverse cardiac remodeling …”
Section: Discussionmentioning
confidence: 99%
“… 53 Exposure to OC mixtures in mice has also shown to be able to intensify oxidative and inflammatory stressors in the heart to overwhelm protective mechanisms allowing for adverse cardiac remodeling. 54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POPs have been related to the development of chronic diseases. Multiple epidemiological studies in different European countries highlighted the strong correlation between the presence of POPs in the circulating system, and the high risk of metabolic and cardiovascular diseases [ 25 , 26 , 27 , 28 , 29 ]. Recently, non-diabetic and diabetic mouse models showed that POPs exposure promotes metabolic syndrome independently of the diet by intensify oxidative and inflammatory stressors, which has for consequence to exacerbate the adverse cardiac remodeling [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data regarding POPs poisoning in humans is generally unavailable since these pollutants tend to cause chronic health effects. POPs presence in any human specimens has been known to cause human health risks, such as type 2 diabetes and gestational diabetes mellitus (21)(22)(23), breast cancer (24)(25), and cardiovascular diseases (26)(27). It is also well known that POPs are considered endocrine-disrupting chemicals (EDCs).…”
Section: Introductionmentioning
confidence: 99%